2018
DOI: 10.1002/ffo2.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of scenario planning as a theory‐driven evaluation tool

Abstract: Theory‐driven evaluation (TDE) is an approach for prescribing an evaluation’s purposes, users and uses, general activities, strategies, and methods in the form of a “program theory.” While widely used, the literature highlights a number of common deficiencies in TDEs, among which is the tendency for underdeveloped program theories because of a lack of specificity on the theory‐creation process, and because the emergent nature of change renders it difficult to identify relevant theory a priori, leading to uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…According to Taplin et al [ 27 ], ToC makes underlying assumptions explicit by delineating the different components: input, outputs, outcomes, and impact [ 28 , 29 ]. ToC can be viewed as both a product and process [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Taplin et al [ 27 ], ToC makes underlying assumptions explicit by delineating the different components: input, outputs, outcomes, and impact [ 28 , 29 ]. ToC can be viewed as both a product and process [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scenarios are widely used as a means of supporting strategic decision making (Bradfield et al, 2005; Derbyshire, 2019). Although there are many definitions of scenario , which can cause “definition confusion” (Spaniol & Rowland, 2018), it is widely regarded as having a plurality and narrative nature (Glenn et al, 2003).…”
Section: Participatory Backcasting and Scenario Design For Sustainabi...mentioning
confidence: 99%
“…The authors reported participants learned to see and understand different perspectives and collaborated on proposing feasible management responses. This holistic approach to the future that seeks to manage uncertainties with stakeholders and compare different possible outcomes of decisions is what separates the method from others such as Theories of Change [18] and Participatory Rural Appraisal [19].…”
Section: Participatory Scenariosmentioning
confidence: 99%